2020
DOI: 10.1016/j.jht.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occupational therapy–led advanced practice hand therapy clinics for patients on surgical outpatient waiting lists at eight Australian public hospitals

Abstract: Resilient safety culture is characterized by continuous improvements to safety performance and the capacity to have foresight, recognizing and anticipating the changing shape of safety risks in complex sociotechnical systems. This study aims to conceptualize resilient safety culture in the construction environment by integrating resilience engineering principles into the concept of safety culture. To fulfill this research aim, a correlational research design was used. Data were collected using questionnaire su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Occupational therapy led hand clinics can reduce wait lists by providing conservative management of chronic hand conditions (Cox et al, 2020). A high patient satisfaction (90%) was associated with seeing an occupational therapist rather than a doctor (Cox et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational therapy led hand clinics can reduce wait lists by providing conservative management of chronic hand conditions (Cox et al, 2020). A high patient satisfaction (90%) was associated with seeing an occupational therapist rather than a doctor (Cox et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational therapy led hand clinics can reduce wait lists by providing conservative management of chronic hand conditions (Cox et al, 2020). A high patient satisfaction (90%) was associated with seeing an occupational therapist rather than a doctor (Cox et al, 2020). An Australian study into physiotherapy led clinics providing conservative management of orthopaedic conditions reported that they successfully operated independently in the assessment and management of 66% of patients, with few patients returned to orthopaedic clinics and 77% of the patients satisfied (Pearse et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To manage growing patient numbers, health services are increasingly adopting novel models of care as a strategy to improve treatment access. [11][12][13][14] For instance, triage clinics and therapist-led models of care, where therapists independently make treatment decisions within an agreed clinical decisionmaking framework, have been implemented for the management of musculoskeletal conditions. 11,[14][15][16][17][18][19] Results of retrospective and prospective studies suggest that these models of care have a positive impact on accelerating access to care, reducing the rate of surgery (if implemented prior to surgery) and improving patient outcomes and satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] For instance, triage clinics and therapist-led models of care, where therapists independently make treatment decisions within an agreed clinical decisionmaking framework, have been implemented for the management of musculoskeletal conditions. 11,[14][15][16][17][18][19] Results of retrospective and prospective studies suggest that these models of care have a positive impact on accelerating access to care, reducing the rate of surgery (if implemented prior to surgery) and improving patient outcomes and satisfaction. 1,15,16,20 In these models of care, clinicians are required to independently assess, provide patient education and therapeutic interventions as well as make treatment decisions that are considered within, but more advanced than their typical scope of practice (for example, assessing the need for surgical intervention).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation